Ocorrencia da Marreca Cabocla Dendrocygna autumnalis no noroeste do Río Grande do Sul, Brasil - Guadagnin, Demétrio L.; Dotto, João C.; Burger, Maria I. (El Hornero, 1995)
Este artículo no cuenta con un resumen.